DISPOSAL METHODS OF SOILED DIAPERS IN LOW-INCOME HOUSEHOLDS OF NAIROBI COUNTY IN KENYA - Muia, Virginia Kavuu (IJRDO-Journal of Applied Science, 2018)
The increased use of disposable diapers in Kenya is placing a heavy load on already strained waste management sectors, which are battling with management of huge piles of solid wastes in towns and cities. This study was aimed at determining the soiled diaper disposal methods used by care givers in low income areas of Nairobi County, Kenya, and assessing the level of awareness on the environmental risks associated with improper disposal of soiled diapers. Cross sectional survey design was used to collect data for this study.  Semi-structured questionnaires were administered to a sample population of 87 respondents who were selected using simple random sampling method. The study established a high use of disposable diapers as opposed to recyclable cloth diapers. The results from this study also indicate that the most prevalent method of soiled diaper disposal is together with household garbage which present significant health risks due to the risk of contracting communicable diseases and also exposure to e coli and other associated diseases. Regarding the level of awareness on the environmental risks associated with poor soiled diaper disposal, most people had no information of the health risks they get exposed to when handling these soiled diapers. The study therefore, recommends that the public should be sensitized on the appropriate means of handling soiled diapers and also the need to embrace safer alternatives like elimination communication which involves observing baby excretion signals in order to know when they need to defecate or urinate hence reduce the use of disposable diapers. Policy makers also need to develop and implement policies that aim at controlling improper soiled diaper disposal and enhancing the efficiency in the collection and handling of these diapers.